"Corneal Plication" for the Management of Progressive Corneal Graft Protrusion in Patients With Keratoconus: a New Technique. Issue 3 (March 2022) - Petrelli, Myrsini; Savopol, Hélène; Blavakis, Emmanouil; Petrou, Petros; Droutsas, Konstantinos; Kymionis, George D.
Abstract : Purpose: The purpose of this study was to present a new surgical technique, namely corneal plication, for the management of high astigmatism and progressive corneal graft protrusion after penetrating keratoplasty (PKP) for keratoconus. Methods: New surgical approach description. Results: A 61-year-old woman with a history of bilateral keratoconus was referred to our institute for the management of progressive corneal graft protrusion in her left eye 25 years after PKP. On presentation, the uncorrected distance visual acuity in the involved eye was counting fingers, whereas slit-lamp examination revealed a clear graft with a crescentic area of thinning in the inferior host cornea, extending from 4 to 9 o'clock that resulted in significant graft protrusion and astigmatism. We proceeded with a novel surgical approach that included "folding" and suturing the thinned, diseased corneal tissue and thus creating a form of corneal plication. No intraoperative or postoperative complications were observed, and uncorrected distance visual acuity was 0.32 6 months after the operation. Conclusions: Corneal graft plication may represent a realistic alternative to more invasive procedures, currently used for the management of this long-term post-PKP complication in patients with keratoconus because it is a nonperforating technique that seems to provide satisfactory anatomical and visual outcomes without the need for any tissue excision or regrafting. Abstract : Supplemental Digital Content is Available in the Text.